2017
DOI: 10.1136/bjsports-2016-096836
|View full text |Cite
|
Sign up to set email alerts
|

Eighty-three per cent of elite athletes return to preinjury sport after anterior cruciate ligament reconstruction: a systematic review with meta-analysis of return to sport rates, graft rupture rates and performance outcomes

Abstract: Objectives The primary objective was to calculate the rate of return to sport (RTS) following anterior cruciate ligament (ACL) reconstruction in elite athletes. Secondary objectives were to estimate the time taken to RTS, calculate rates of ACL graft rupture, evaluate postsurgical athletic performance and identify determinants of RTS. Design Pooled RTS and graft rupture rates were calculated using random effects proportion metaanalysis. Time to RTS, performance data and determinants of RTS were synthesised des… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

19
289
5
13

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 380 publications
(326 citation statements)
references
References 59 publications
(64 reference statements)
19
289
5
13
Order By: Relevance
“…These figures are broadly comparable to the findings of Lai et al, 6 who in a recent systematic review reported that a mean of 83% of elite athletes were able to return to the preinjury level of sport; they took a mean time of 6 to 13 months to do so, and the pooled graft rupture rate was 5.2%. However, it is important to note that both the return to sport rates (42%-100%) [22][23][24] and the graft rupture rates (0%-19.3%) 23,[25][26][27] reported in the studies included by Lai et al 6 varied broadly. This highlights the fact that the risk of graft rupture is higher in certain sports or even certain positions within the same sport.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…These figures are broadly comparable to the findings of Lai et al, 6 who in a recent systematic review reported that a mean of 83% of elite athletes were able to return to the preinjury level of sport; they took a mean time of 6 to 13 months to do so, and the pooled graft rupture rate was 5.2%. However, it is important to note that both the return to sport rates (42%-100%) [22][23][24] and the graft rupture rates (0%-19.3%) 23,[25][26][27] reported in the studies included by Lai et al 6 varied broadly. This highlights the fact that the risk of graft rupture is higher in certain sports or even certain positions within the same sport.…”
Section: Discussionsupporting
confidence: 87%
“…individuals who return to elite sport, there is evidence that they may not be used by their team in competition as frequently, that their earning potential is significantly reduced, and that their overall careers may be shorter than age-matched controls. 4,5 However, in contrast to the general population, the rate of return to sport in professional athletes is very high, 6 but this also means that they are at significantly greater risk of ACL graft rupture when compared with those with a sedentary lifestyle. 7,8 Walden et al 9 highlighted that the rates of ACL graft rupture were unacceptably high in professional soccer athletes, and these concerns are mirrored in numerous reports of graft rupture rates between 18% and 20% in high-risk populations.…”
mentioning
confidence: 99%
“…Elite athletes are more than twice as likely to return to preinjury sport than recreational athletes,41 and a new meta-analysis showed that 83% of elite athletes returned to preinjury sport after ACLR 15. In our study we did not use the broad term return to sport.…”
Section: Discussionmentioning
confidence: 89%
“…La lesiĂłn deportiva parece adquirir gran importancia en el interĂ©s de los investigadores, sobre todo en los Ășltimos años (Lai, Ardern, Feller, & Webster, 2017;Slimani et al, 2018). AdemĂĄs, la lesiĂłn empieza a ser estudiada desde diferentes perspectivas como los aspectos fĂ­sicos, fisiolĂłgicos, biomecĂĄnicos, psicolĂłgicos y, evidentemente, mĂ©dicos (Bahr & Krosshaug, 2005;Brewer & Redmond, 2016;Udry & Andersen, 2008).…”
Section: Introductionunclassified